SACRAMENTS AND RITUALS - Kadankavil, Thomas (Journal of Dharma, 1984)
All forms of popular religions have some sort of sacraments and rituals. Christianity, which seeks to speak of religious reality with more theological precision, makes a distinction between the Sacrament and Sacramental, the former being understood as a visible means or channel that mediates inner grace and the latter as a ritual having the force or efficacy of a sacrament. The Christian tradition speaks of seven sacraments, liturgical enactment of the Eucharistic sacrifice, and a number of other rituals symbolically presented, interpreted and understood.